THE EFFICACY AND SAFETY OF ANTI-TNF A TREATMENT IN ANKYLOSING SPONDYLITIS PATIENTS WITH LATE ONSET COMPARED TO THOSE WITH ADULT ONSET; THE DATA FROM TURKBIO REGISTRY - Uslu, Sadettin; Can, Gercek; Cefle, Ayse; Yilmaz, Sema; Kocaer, Sinem Burcu; Inel, Tuba Yuce; Onen, Fatos (Bmj Publishing Group, 2019)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 12-15, 2019 -- Madrid, SPAIN